2021
DOI: 10.1021/acsomega.1c02193
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Flow State of Circulating Cooling Water for the Industrial Heat Exchange Tube in the Electromagnetic Anti-Fouling Process

Abstract: Comparing with the traditional chemical and physical method, the electromagnetic water treatment technology draws more attention of researchers for its advantages of easy application, small investment, low cost, and being pollution free in recent years. However, due to the less study of the formation process and adhesion of fouling on the surface of heat exchange equipment, the electromagnetic anti-fouling performance cannot be well evaluated. This paper studies the numerical simulation of the flow states of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, solving such time-varying fields accurately is highly challenging. Based on the works of Xiong Lan, Hermann A. Haus, and others [8,10,11] , the electromagnetic field inside a coaxial processing chamber can be considered a quasistatic field under certain conditions, enabling the obtainment of accurate analytical data. The conditions for a quasistatic field are as follows: within the time frame of our interest, the electromagnetic waves in the studied system are stable and rapidly varying.…”
Section: Basis Of a Quasi-static Methods For Coaxial Processing Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, solving such time-varying fields accurately is highly challenging. Based on the works of Xiong Lan, Hermann A. Haus, and others [8,10,11] , the electromagnetic field inside a coaxial processing chamber can be considered a quasistatic field under certain conditions, enabling the obtainment of accurate analytical data. The conditions for a quasistatic field are as follows: within the time frame of our interest, the electromagnetic waves in the studied system are stable and rapidly varying.…”
Section: Basis Of a Quasi-static Methods For Coaxial Processing Cavitymentioning
confidence: 99%
“…Through a review of relevant literature, it has been found that factors such as the size of the processing cavity, waveform of the excitation source, and anode-cathode radius ratio have an impact on the electromagnetic field inside the coaxial processing cavity, thereby influencing the descaling effects. The temporal variation and complex structure of the electromagnetic field within the coaxial processing cavity introduce numerous influencing factors, leading to the current instability in the descaling performance of the processing cavities [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that particle deposition was affected by the turbulence pattern created by the ribs, secondary flow, interception on the windward side of the ribs, particle rebound, and gravity settling. Yan et al [26] performed numerical simulations of the flow of circulating cooling water in straight and U-shaped heat exchange tubes. The results showed that whether the surface of the heat exchange tube was magnetic or not had a significant effect on its fouling resistance.…”
Section: Introductionmentioning
confidence: 99%